Clinical features and prognosis of primary tracheal small cell carcinoma: a population-based analysis - Chen, Kun; Yang, Zhihao; Zhang, Xinbo; Zhao, Tianhao; Zhang, Xiang; Li, Wenfeng; Yu, Shanshan; Xie, Deyao; He, Zhifeng; Cheng, Dezhi (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2020)
Background: Primary tracheal small cell carcinoma (SCC) is an uncommon malignancy; therefore, its clinical features and prognosis are still unclear. Methods: We used the population-based Surveillance, Epidemiology, and End Results (SEER) database to elucidate the clinical features and prognosis of primary tracheal SCC. The clinical features were assessed by using the chi-square test. Overall survival (OS) was computed using the Kaplan-Meier method, and a Cox proportional hazards analysis was performed to evaluate the prognostic factors. Results: From 1973 to 2015, 1,392 primary tracheal tumor cases were reported in the SEER database, 75 (5.4%) of which were SCC. Age, sex, race, extent of disease, lymph node involvement, surgery and radiation treatment were similar between patients with SCC and those with squamous cell carcinoma (SQC), but patients with SCC were more likely to receive chemotherapy (65.8% vs. 28.2%, respectively; P